((a-1)/(a+1) -(a+1)/(a-1)) : 2a/(1-a)

jumalieva03 jumalieva03    2   11.05.2020 11:58    0

Ответы
PolinaGetto PolinaGetto  18.08.2020 14:17

Объяснение:

(\frac{a-1}{a+1} -\frac{a+1}{a-1} ):\frac{2a}{1-a^{2} } =\frac{(a-1)^{2} -(a+1)^{2} }{(a+1)(a-1)} :\frac{2a}{1-a^{2} }=\frac{(a-1+a+1)*(a-1-a-1) }{(a+1)(a-1)} *\frac{1-a^{2} }{2a} =\\=\frac{2a*(-2)}{(a+1)*(a-1)}*\frac{1-a^{2} }{2a} =\frac{-4a*(-(a^{2} -1)}{2a*(a+1)*(a-1)} =\frac{4a*(a-1)(a+1)}{2a*(a+1)*(a-1)}=2.

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра